ANALYSIS OF PENSION FUND CASH DISBURSEMENT ACCOUNTING SYSTEM TO SUPPORT INTERNAL CONTROL - Gelisia Juanita Angrum; . Suhadak; . Kertahadi (Jurnal Administrasi Bisnis, 2013)
Pension fund is an alternative choice in providing welfare assurance to employees. The assurance is possible to solve the problems that arise along employee’s risk in the work field. These risks include the risk of losing a job, less productive age (elderly), and accident that resulted in physical disability or even death. To support the pension fund cash disbursement distribution, it needed a well adequate internal control structure and required agencies/companies that are competent for distributing the pension funds. The research objectives is to describe the implementation of the pension fund cash disbursement accounting system and procedure, to analyze the implementation of the pension fund cash disbursement accounting system and procedure in supporting internal control, to identify the strengths and weaknesses of the implementation internal control system of accounting processes on pension fund cash disbursement. Based reseach finding implementation of the pension fund cash disbursement accounting system and procedure and implementation of the pension fund cash disbursement accounting system and procedure in supporting internal control is good enough where a part pension, finance, accounting was standing alone. The strengs of this company is authorization of duties, double recording with computer program, delivery service pension fund. The weaknesess of this company is where no internal audit, each section stand is not in the department, and less of employee. Keywords: Pension Fund, Cash Disbursement, Internal Control